2015
DOI: 10.1128/aac.01139-15
|View full text |Cite
|
Sign up to set email alerts
|

3-Halo Chloroquine Derivatives Overcome Plasmodium falciparum Chloroquine Resistance Transporter-Mediated Drug Resistance in P. falciparum

Abstract: Polymorphism in the Plasmodium falciparum chloroquine resistance transporter (PfCRT) was shown to cause chloroquine resistance. In this report, we examined the antimalarial potential of novel 3-halo chloroquine derivatives (3-chloro, 3-bromo, and 3-iodo) against chloroquine-susceptible and -resistant P. falciparum. All three derivatives inhibited the proliferation of P. falciparum; with 3-iodo chloroquine being most effective. Moreover, 3-iodo chloroquine was highly effective at potentiating and reversing chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We synthesized a chloroquine photoaffinity labelled analog with minimal modification of the quinoline structure. The aryl azide was placed at the 3-position, a position that our group has previously taken advantage of [ 5 , 6 ]. The strategy for this preparation is to use an Ullman coupling for the formation of a C sp2 —heteroatom bond at the 3-position [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized a chloroquine photoaffinity labelled analog with minimal modification of the quinoline structure. The aryl azide was placed at the 3-position, a position that our group has previously taken advantage of [ 5 , 6 ]. The strategy for this preparation is to use an Ullman coupling for the formation of a C sp2 —heteroatom bond at the 3-position [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (500 MHz, chloroform-d) δ 2.52 (q, J = 7.2 Hz, 4H), 2.40 (d, J = 6.5 Hz, 5H), 1.51-1.42 (m, 3H), 1. 34 N4-(7-chloroquinolin-4-yl)-N1,N1-diethyl-N4-methylpentane-1,4-diamine (6) The mixture of 4,7-dichloroquinoline (500 mg, 2.5 mmol) and N 1 ,N 1 -diethyl-N 4methylpentane-1,4-diamine (652.6 mg, 3.8 mmol, 1.5 equiv.) were placed in a microwave flask with p-toluenesulfonic acid (816 mg, 4.3 mmol, 1.7 equiv.).…”
Section: N-(5-(diethylamino)pentan-2-yl)formamide (9)mentioning
confidence: 99%
“…It has been found that a variety of compounds without fixed chemical properties can restore the sensitivity to CQ ( de Souza et al, 2019 ). These compounds, when co-administrated with CQ, were observed to increase the sensitivity of some CQ resistant P. falciparum strains in vitro ( Ch'ng et al, 2013 ; Deane, Summers, Lehane, Martin, & Barrow, 2014 ; Edaye, Tazoo, Bohle, & Georges, 2015 ; Kashyap et al, 2018 ). The major mechanism involved is the inhibition of the active drug efflux pump pfcrt ( van Schalkwyk & Egan, 2006 ).…”
Section: Cq and Hcq In The Treatment Of Malariamentioning
confidence: 99%
“…Numerous chloroquine derivatives have been prepared in order to overcome Plasmodium resistance, the main problem in malaria treatment (see, for example, refs. [14][15][16] or in finding new anticancer agents (refs. 17-20).…”
mentioning
confidence: 99%